Highly photosensitive furan acrylate derivatives and their solid-state photopolymerization. (16th August 2022) - Wang, Jin; Wang, Yuanlu; Liu, Bingchen; Fu, Tao
Abstract : Highly photosensitive multifunctional furan acrylate monomers synthesized from biomass furfural can be photopolymerized into polyesters without photoinitiators and solvents. Abstract : A bifunctional diethylene glycol difuran acrylate (DEFA) and a trifunctional trimethylolpropane trifuran acrylate (TMFA) monomer for solid-state photopolymerization were synthesized from a biomass material, furfural. High molar extinction coefficients in the order of 10 4 indicate the good UV absorption properties of both monomers. The photopolymerization kinetics studies show that DEFA achieves a maximum polymerization rate ( R p ) in 54 s and TMFA in 35 s without photoinitiators, and the maximum double bond conversion (DBC) reached 88% for DEFA and 78% for TMFA, which proves that they have high photosensitivity. The addition of the 2, 4-dinitroaniline sensitizer increases the maximum DBC, but increases the maximum R p markedly. The high crystallinity of DEFA and TMFA is prone to photodimerization and forms an amorphous polymer. Both the linear polyester from DEFA and the crosslinked polyester from TMFA have good thermal oxidation stability. Therefore, we developed a strategy to produce highly sensitive monomers for the application of photosensitive materials that polymerize quickly without photoinitiators and solvents.